âPENGARUH PEMBERDAYAAN DAN KARAKTERISTIK PEKERJAAN TERHADAP KINERJA PEGAWAI MELALUI MEDIASI ORGANIZATIONAL CITIZENSHIP BEHAVIOR (STUDI PADA DINAS PEKERJAAN UMUM KABUPATEN REMBANG)â - Kapti Prastiyo Aji, 1252020233 (Jurnal Mahasiswa Pasca Sarjana, 2015)
This study aims to examine the effect of Empowerment and Job Characteristics on employee performance through Mediation Organizational Citizenship Behavior (OCB) (Studies in the Department of Public Works Rembang). This study used a sample of 149 respondents, with tenure from less than 5 tahunsampai more than 15 years, and the respondents educational level ranging from elementary school to the S-2. Engineering test data used in this study include testing the validity of the KMO value requires variable empowerment, job characteristics, organizational citizenship behavior (OCB) and the performance of employees is greater than 0.5, reliability testing by requiring Cronbachs alpha greater than 0.7, multiple regression analysis and t test to test and prove the research hypothesis, and test mediation aims to find out if there is mediation or not. The data is processed using analytical technique with the help of Statistical package for the Socialsciencess (SPSS). The results showed that the partial influence of independent variables on the dependent variable showed that; (1) that empowerment has a positive impact and no significant effect on organizational citizenship behavior (OCB; (2) Characteristics of work has positive and significant influence on organizational citizenship behavior (OCB; (3) empowerment has a positive impact and no significant effect on employee performance; ( 4) Characteristics of the work has a positive and significant influence on employee performance; (5) Organizational citizenship behavior (OCB) has a significant negative influence on employee performance. Keywords: Empowerment, Job Characteristics, Organizational Citizenship Behavior (OCB) and employee performance.